2012
DOI: 10.2139/ssrn.2162023
|View full text |Cite
|
Sign up to set email alerts
|

Regional Trade Agreements and Domestic Labour Market Regulation

Abstract: The International Labour Office welcomes such applications. Libraries, institutions and other users registered with reproduction rights organizations may make copies in accordance with the licences issued to them for this purpose. Visit www.ifrro.org to find the reproduction rights organization in your country.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 28 publications
0
21
0
1
Order By: Relevance
“…More recently, some research (e.g. the IJHRM special issue on The state, public policy and the renewal of HRM edited by Häberli, Jansen, & Monteiro, 2012;Kretsos & Martínez Lucio, 2013;Ollier-Malaterre, McNamara, Matz-Costa, PittCatsouphes, & Valcour, 2013;Williams, Heery, & Abbott, 2011) has engaged with this complexity, raising the importance of exploring the role of regulation at different levels: from attention to domestic labour markets, such as the context of devolved regimes, to the organisational level through attention to the renewal of HRM. These discussions highlight the importance of understanding not only the transformations in dynamics and processes of work and employment, but also the nature of and the role played by social actors, and ultimately the implications of these changes on the way work settings operate and are regulated.…”
Section: The Regulation Of Work and Employment And I/chrmmentioning
confidence: 99%
“…More recently, some research (e.g. the IJHRM special issue on The state, public policy and the renewal of HRM edited by Häberli, Jansen, & Monteiro, 2012;Kretsos & Martínez Lucio, 2013;Ollier-Malaterre, McNamara, Matz-Costa, PittCatsouphes, & Valcour, 2013;Williams, Heery, & Abbott, 2011) has engaged with this complexity, raising the importance of exploring the role of regulation at different levels: from attention to domestic labour markets, such as the context of devolved regimes, to the organisational level through attention to the renewal of HRM. These discussions highlight the importance of understanding not only the transformations in dynamics and processes of work and employment, but also the nature of and the role played by social actors, and ultimately the implications of these changes on the way work settings operate and are regulated.…”
Section: The Regulation Of Work and Employment And I/chrmmentioning
confidence: 99%
“…I employ the following econometric specification, inspired by Häberli et al (2012) and also distinguishing RTAs with labor clauses from those without labor clauses: . 47 The variable is also expressed as the 45 This specification differs from the one employed in Häberli et al (2012) that includes dummies indicating the region and income group of each country. The current research includes individual country dummies considering the nature of the data for the labor condition variables L it sourced from the ILO statistics.…”
Section: Effects On Labor Conditionsmentioning
confidence: 99%
“…The author therefore considers that within-country comparisons using an individual country fixed-effect approach is suitable to the estimation in the current research. On the other hand, Häberli et al (2012) specification. These variables, inspired by Häberli et al (2012), are defined as follows: for all the countries and years, however, the sample valid for the empirical analysis does not cover all of these countries and years (i.e., the sample is an unbalanced panel), and observations valid for each regression are further limited.…”
Section: Effects On Labor Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent ILO study (Häberli et al, 2012) has shown empirical evidence that regional integration among industrialized countries tends to undermine the application of ILO core labor standards. If these findings are considered as relevant in the context of TTIP the European Commission and governments of EU countries and the US -possibly also of Canada and Mexico -should adopt rules that make sure that ILO labor standards are not undermined.…”
Section: Policy Issuesmentioning
confidence: 99%